Trabalho escravo: reflexões sobre a escravidão urbana contemporânea no Brasil - Nascimento, Maria Daniele Silva do (2015)
The Labour Law is stage for social revolutions, thus the situations that arise in the social environment are reflected directly in the context of labor relations. The evolution of society promotes social differentiation, for Marx, men build for themselves in the production of their livelihoods. This is how men organize themselves socially and establish social relations of production. This research is about highlighting the Constitutional Principle of Human Dignity as justifying the systematic protective of the Labor Law, emphasizing the importance of the social value of work as a foundational element of the economic and social order, considering the human aspect of the worker. the problem about the definition of human slavery in Brazil now-a-days. Its proposal is to define slavery-like practices based on the most important principle of a democratic state: the principle of human dignity. It pretends to claim that the idea of human slavery conceives not only those situations where freedom is denied, but also those where work takes place without the minimum conditions of dignity. The paper talks about the historical elements of slavery since old times until today, showing some features that set them apart, and later deals specifically with the contemporary Brazilian slavery, stating that its existence harms human dignity itself and thus it must be eradicated and prevented. And identify in the evolution of public policies to eradicate slave labor the different actors and dynamics of relations between them.